One-stage partial nitritation-anammox treatment of reject water from high-solid-sludge anaerobic digestion with thermal hydrolysis pretreatment: Inhibition and system recovery. Issue 3 (June 2022) - Cui, Rongrong; Gong, Hui; Xu, You; Xu, Enhui; Yang, Dianhai; Gu, Guowei; Dai, Xiaohu
Abstract: This study investigated the performance of a one-stage partial nitritation-anammox (PN/A) system for the treatment of reject water from high-solid-sludge anaerobic digestion with thermal hydrolysis pretreatment (THP-AD). The proportion of reject water was gradually increased (10.8%, 23.2%, 36.4%, 73.7% and 100%) during the 90-day operation. The nitrogen loading rate (NLR) reached 0.44 kg N/m 3 /d using 73.7% reject water as influent, while it decreased to only 0.15 kg N/m 3 /d with 100% reject water. Meanwhile, sludge particles with diameters < 180 µm became the largest granulometric fraction. Microbial community structure analysis indicated that the relative abundances of functional microorganisms became extremely low; e.g., 0.05% and 0.5% for Nitrosomonas and Candidatus Brocadia, respectively. An additional 47-day experiment was performed using only the anammox stage to evaluate the inhibition impacts of organics. This was fed with reject water with partial ammonia nitrogen stripping and nitrite nitrogen addition for the first 38 days and PN-treated reject water for days 39–47. Reject water with an 80% raw organic content demonstrated severe inhibition, with the NLR dropping from 1.27 kg N/m 3 /d to 0.27 kg N/m 3 /d. This, could be partially restored to 0.93 kg N/m 3 /d when the influent was pretreated by PN. It appears that the biodegradable organic matter inhibited the one-stage PN/A system more than the non-biodegradable fraction. After removal of biodegradable organics, the NRR of the anammox system recovered, indicating that two-stage PN/A has greater advantages in THP-AD reject water treatment than a one-stage PN/A system. Graphical Abstract: ga1 Highlights: Decreasing dilution of THP-AD reject water in the influent reduced one-stage PN/A activity. Degranulation of granular anammox sludge occurred when treating THP-AD reject water. The abundance of AOB and AMX bacteria was low when treating undiluted THP-AD. PN pretreatment alleviated inhibition of anammox activity. SCOD value couldn't directly explain the inhibition of anammox activity.